Diagnosis of complex mixture toxicity in sediments: Application of toxicity identification evaluation (TIE) and effect-directed analysis (EDA). (June 2018) - Li, Huizhen; Zhang, Jie; You, Jing
Abstract: Determining causality of sediment toxicity is of great importance in aquatic risk assessment, but there are tremendous challenges due to joint toxicity of trace pollutants in complex sediment matrices. Two approaches, namely toxicity identification evaluation (TIE) and effect-directed analysis (EDA) have been developed. Conventional sediment TIEs take the advantage of environmental relevance by using whole organism bioassays; however, they suffer from lack of effective methods for specifically identifying major contributors as it typically only evaluates contaminant class rather than specific contaminants. Alternatively, EDA is a powerful tool in identifying causes of sediment toxicity with sophisticated fractionation and chemical analysis of targeted and non-targeted non-polar organic toxicants, but it is not always environmentally relevant due to the use of in-vitro bioassays and exhaustive solvent extraction. An integrated TIE and EDA method would provide an environmentally relevant and toxicant specific approach to effectively determine causality of sediment toxicity by combining the merits of the two methods. Bioavailability-based extraction and dosing techniques are recommended to be incorporated into the integrated method to improve the accuracy of toxicity diagnosis. Besides considering bioavailability in the integrated TIE and EDA approach, the premise of adverse outcome pathways should also be considered. Generally speaking, both TIE and EDA have focused on adverse effects at cellular and organism levels. The addition of trait-based approaches in screening multiple toxicological endpoints helps to extend effects on cellular and organism levels to population level, and provides a better understanding of potential impacts to the community and ecosystem. The outcome pathway underlies the critical role of determining causality in interpreting impacts of complex mixtures to benthic community and aquatic ecosystem. Graphical abstract: Image 1 Highlights: TIE and EDA are powerful effect-based tools in diagnosing toxicants in mixtures. Integrating TIE and EDA are more environmental relevant and toxicant specific. Bioavailability-based approaches increase accuracy in toxicant identification. Tiered effect-based tools help to elucidate toxicants of known and unknown identity. Abstract : A tiered effect-based tool with the consideration of bioavailability is proposed to diagnose the causality of sediment toxicity after reviewing the benefits and drawbacks of TIE and EDA.